Medicolegal Investigation in a Crushed Injury in Lower Limb due to Road Traffic Accident - Taufik Suryadi; Kulsum Kulsum (Jurnal Kedokteran Syiah Kuala, 2022)
The prevalence and incidence of traffic accidents resulting in injuries to the extremities are still high enough so that the morbidity and mortality rates increase each year. Extremity injuries that occur as a result of traffic accidents cause damage to bones, muscles, joints and also in blood vessels, which can cause massive bleeding which can result in haemorrhagic shock and lead to death. A reported case of a 41-year-old woman suffered a traffic accident that resulted in her left leg being crushed. According to the medicolegal system in Indonesia, every case of a traffic accident must be made a simultaneous examination between clinical medical aspects and clinical forensics. Medical evidence was collected to produce a medicolegal investigation report. In this case an analysis of how predicted traffic accident events, the impact of trauma, the degree of qualification of injuries to the estimated threat of punishment for the perpetrators who caused injury to victims due to traffic accidents involving extremity.